Institutional enforcement, labor-market rigidities, and economic performance - César Calderón; Alberto Chong; Gianmarco León (Inter-American Development Bank, Research Department, 2006)
This paper compares non-enforceable and enforceable measures of labor rigidities as a measure of the quality of labor institutions, and tests whether such labor rigidities are conducive to long-run growth. We find that non-enforceable labor regulations do not have a bearing on economic growth, but enforceable labor regulations do. In fact, when using a GMM-IV method for a panel data of countries during the period 1970-2000 that accounts for weak endogeneity, we find that such a link is negative and statistically significant. It appears that excessive labor rigidities are thus negatively linked with long-run economic growth.
Keywords: O10; E60; J08; O40; 330; Institutions; Enforcement; Labor Rigidities; Growth; GMM-IV; Arbeitsmarkttheorie; Lohnrigidität; Momentenmethode